Gold, wax and egg : the yellow color as tertium comparationis in medieval French - Blanco, Xavier (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
In this paper, we analyze the intensive comparisons applied to medieval French adjectives with the meaning ‘yellow’ or with closely related meanings. On the basis of the concept of collocation defined by the Explanatory and Combinatorial Lexicology (Meaning- Text Theory), we study the second terms of these comparisons in successive sections. A first section presents the concept of collocation. The second section is dedicated to the second term of comparison ‘gold’. The third section deals with the term ‘wax’ and the fourth section deals with the term ‘egg yolk’. A fifth section regroups other less frequent second terms of the comparison, such as ‘kite spawn’, ‘oriole feather’ or ‘Spanish broom’. This paper is integrated in the COLINDANTE research project (I+D+i PID2019-104741GB-100, Ministry of Science and Innovation, Spain) and is part of a series of works that describe intensive comparisons based on the names of colors in medieval French.